The Factors Influencing Meal Satisfaction in Older Adults: A Systematic Review and Meta-analysis - Kyung Hee Lee; JinA Mo (Elsevier, 2019)
Purpose: The aim of this study was to identify factors influencing meal satisfaction in older adults. Methods: Authors searched four databases Ovid MEDLINE, Ovid EMBASE, the Cochrane Library, and KoreaMed using the following key search terms: "(elderly-mp. OR aged), AND (meal OR food OR eating OR feeding), AND satisfaction." Only articles published between January 1946 and May 2018 were considered. The preferred reporting items for systematic reviews and meta-analyses guidelines were adopted for quality assessment. The authors ultimately selected 7 of 1,695 references for review and meta-analysis. Results: A meta-analysis was conducted to determine the factors influencing meal satisfaction in older adults aged more than 60 years. The results showed that meal satisfaction was low when age increased and the individual was served frozen meals. Satisfaction with meals was high when food choices were available and individuals were served high-quality food and when the food smelled and tasted good or was personally tailored. Satisfaction was also high when individuals ate with their families. Moreover, meal satisfaction seemed to be influenced by physical health, whereas it did not show a significant correlation with mental health. Conclusion: Intending to improve the quality of life of older adults by increasing their meal satisfaction, the authors pointed out factors that institutions should attend to when providing meals to older adults. To contribute to the lack of any existing conceptual and theoretical framework in this field, further steps to be taken by the authors shall involve concept analysis that would assist in building a conceptual framework. Keywords: aged, meals, meta-analysis, personal satisfaction